(untitled) (Annals of Bangladesh Agriculture, 2023)
An experiment was conducted at the research field and the laboratory of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur-1706, Bangladesh from October 2018 to March 2019 to investigate the effect of organic amendments and arbuscular mycorrhizal fungi (AMF) on growth, yield and quality of strawberry var. BARI Strawberry-2. The experiment was laid out in RCBD design with three replications taking into eight treatments including control viz., T1: vermicompost (324 g/pot), T2: biochar (324 g/pot), T3: AMF (324g/pot), T4: vermicompost (162 g/pot) + biochar (162 g/pot), T5: biochar (162 g/pot) + AMF (162 g/pot), T6: vermicompost (162 g/pot) + AMF (162 g/pot), T7: vermicompost (108 g/pot) + biochar (108 g/pot) + AMF (108 g/pot) and T8: control (no manure or AMF). Results of the study revealed that the highest plant height (18.40 cm), number of leaves/plant (37.00), leaf area (578.60 cm2), root length (24.50 cm), fresh and dry weight of root (30.00 g and 12.5 g) and shoot (131 g and 41.00 g), number of flowers (32.67/plant) and fruits (22.33/plant), single fruit weight (21.60 g) and yield/plant (401.99 g) were recorded in T6 treatment which was significantly superior to all other treatments. Among the fruit nutrient and mineral contents, ascorbic acid (36.20 mg/100 g), total sugar (9.10 g/100 g), Ca (11.87 mg/100 g), Mg (36.67 mg/100 g) and K (73.33 mg/100 g) were also measured maximum in T6 treatment. On the other hand, TSS (8.49 %) and water percentage in fruit (66.95 %) were found significantly higher in T7 and T4 treatments, respectively while the lowest was estimated in the control. A significant influence of T6 treatment [vermicompost (162 g/pot) + AMF (162 g/pot)] on growth, yield and qualitative characters was observed. Therefore, vermicompost and AMF combination has reflected a positive impact on good quality strawberry production. However, it needs to be investigated under the open field condition before conferring recommendation to the end users. Ann. Bangladesh Agric. (2022) 26 (2) : 71-82